IMPROVING THE PROCESS OF TRAINING OF SALES PERSONNEL IN UKRAINIAN COMPANIES - YEVTUSHENKO, Victoria; SHUBA, Tetiana; LISENYI, Yevhen; ROZHENKO, Ilya (Herald of Khmelnytskyi National University. Economic sciences, 2023)
The article is devoted to the problem of improving the process of training sales personnel in Ukrainian companies. The stages of implementation of sales training in Ukrainian companies are considered. The process of developing educational programs is considered in detail. All types of group and individual training programs were analyzed. The advantages of training sales personnel for Ukrainian companies have been determined. The workforce plays a special role in the activity of any enterprise. At the same time, it should be noted that in companies that aim to enter foreign markets, human resources become extremely important. Personnel selection, motivation, training, adaptation and other elements of management become even more important. Sales training is an organized program to improve the skills, abilities, attitudes and performance of sales personnel to achieve sales objectives through best practices. It is organized to support the sales performance of the sales force to make them adapt strategically to changes in sales practices to also support the profits of the enterprise. It is a process developed with sales personnel to bridge the gap that exists between what salespeople have and what the sales force requires in order to achieve the desired sales results in the sales environment. This gap can be closed because sales training allows salespeople to learn job-related concepts and develop skills and attitudes that will undoubtedly increase their productivity. In fact, it helps salespeople adapt their behavior to win the sales race in the face of new challenges. The goal of a sales training program is to improve sales performance and achieve the best possible sales success. It helps the sales company/executive who wants to improve their sales skills. These are the most common goals, but they vary widely depending on the types of skills that salespeople lack, the types of training programs, and the environment.